Clinical manifestations and management of Tityus species envenoming: A systematic review (Research, Society and Development, 2024)
Scorpionism, or a clinical picture of envenomation caused by a scorpion sting, is a public health problem in South America. The manifestations clinical and management are varied and complex and there is still no consensus in the literature on these aspects. The aim of this systematic review is to describe the clinical manifestations, as well as treatment after scorpion envenomation by Tityus species. The online databases of PubMed, Scopus, Web of Science, and SciELO were systematically searched for relevant publications until march 2022. No language and age restrictions were imposed. The literature search generated 476 references and 23 studies were included in the systematic review, according to the inclusion criteria of this review. The number of participants studied was 7,781. The specie Tityus serrulatus was found in more studies. The time elapsed between the accident and medical care ranged from 15 minutes to more than 6 hours. The treatments performed in selected studies include scorpion antivenoms, corticosteroids, anesthetics, antiemetics agents, inotropics, antihypertensives and benzodiazepines drugs. In six studies, fatal cases were observed in five children aged 1 to 6-y and one in children < 14 y. We concluded that management of Tityus species envenoming is supportive and focused on the patient’s symptoms. In severe cases, antivenoms, if available, are indicated. Medications to monitor vagal and adrenergic symptoms are encouraged. This study has the potential to help professionals who deal with envenomations caused by the genus Tityus.